2021
DOI: 10.3390/land10121314
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ageing, Gender and Environmental Problems in Subjective Well-Being

Abstract: This paper studies the relationship of factors such as ageing, gender and environmental problems included in the quality of life (QoL) with the subjective well-being represented by the life satisfaction (LS) indicator of the citizens of 33 European countries. To do so, it uses the LS of a country’s citizens as the dependent variable; ageing, gender and environmental variables as independent variables; and other factors included in the QoL indicators and macroeconomic factors as control variables. Analysis uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Such knowledge is necessary to match the goals of care services to their expectations. An analysis of the life satisfaction indicator (LS) indicates that the debt of older people in Europe is significantly and positively related to low LS levels [62]. The opposite is true for the incomes of people aged 65 and over.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such knowledge is necessary to match the goals of care services to their expectations. An analysis of the life satisfaction indicator (LS) indicates that the debt of older people in Europe is significantly and positively related to low LS levels [62]. The opposite is true for the incomes of people aged 65 and over.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The China Ecological Environment Status Bulletin released by the Ministry of Ecology and Environment in 2022 shows that 126 of the country's 338 cities above prefecture level still have air quality exceeding the standard. These pollutants can enter the human body through the respiratory tract, resulting in disorders in residents' self-regulatory functions and a decline in immunity, bringing health risks, illness and even death to residents [3][4][5][6]. The 2010 Global Burden of Disease study showed that air pollution is the fourth largest health risk factor for Chinese people [7].…”
Section: Introductionmentioning
confidence: 99%
“…In modeling choices, linear models have been widely used, such as ordinary least squares [44]. In addition, logistic regression models have been applied to assess the relationship between residential satisfaction and place attachment [45].…”
Section: Introductionmentioning
confidence: 99%